Inovasi Kolaboratif Dalam Pembentukan Peraturan Perundang-Undangan: Optimalisasi Teknologi Untuk Meningkatkan Partisipasi Publik Dalam Legislasi - Prasojo, Hermawan (UI Scholars Hub, 2025)
Meaningful public participation in the legislative process in Indonesia is a fundamental element in fostering an inclusive and transparent democracy. Despite the legal mandate for public involvement, as outlined in Law No. 13 of 2022 and Constitutional Court Decision No. 82/PUU-XXI/2023, such participation often remains formalistic and limited in practice. This article highlights the potential of digital technology, particularly the concept of CrowdLaw, as an alternative approach to enhancing public engagement. Case studies from Estonia, Iceland, and Brazil demonstrate that digital participation can effectively increase public involvement and improve the quality of legislative outcomes. With sufficient infrastructure and improved digital literacy, Indonesia is well-positioned to harness technology to create a more inclusive legislative process. However, challenges such as unequal access to technology and low levels of digital literacy across much of the population hinder this effort. Therefore, this article recommends strengthening public participation at all stages of the legislative process, implementing policies that support the sustainable adoption of CrowdLaw, enhancing digital infrastructure, developing user-friendly participation platforms, and expanding digital literacy education to ensure more equitable and substantive public engagement in legislative processes